Photobiomodulation in diabetic wound healing: A review of red and near‐infrared wavelength applications - Oyebode, Olajumoke; Houreld, Nicolette Nadene; Abrahamse, Heidi (Cell biochemistry and function, 2021)
The development of a painless, non‐invasive, and faster way to diabetic wound healing is at the forefront of research. The complexity associated with diabetic wounds makes it a cause for concern amongst diabetic patients and the world at large. Irradiation of cells generates a photobiomodulatory response on cells and tissues, directly causing alteration of cellular processes and inducing diabetic wound repair. Photobiomodulation therapy (PBMT) using red and near‐infrared (NIR) wavelengths is being considered as a promising technique for speeding up the rate of diabetic wound healing, eradication of pain and reduction of inflammation through the alteration of diverse cellular and molecular processes. This review presents the extent to which the potential of red and NIR wavelengths have been harnessed in PBMT for diabetic wound healing. Important research challenges and gaps are identified and discussed, and future directions mapped out. This review thus provides useful insights and strategies into improvement of PBMT, including its acceptance within the global medical research community.